Synthesis, Characterization and Antimicrobial Studies of Some Mixed Ligand Complexes of Lanthanide(III) Ions - Rajendran, G.; Sreeletha, G.S. (Asian Journal of Chemistry, 2012)
The present investigation is concerned with the synthesis, characterization and antimicrobial studies of some mixed ligand complexes of lanthanide(III) ions, viz., La3+, Pr3+, Nd3+, Sm3+, Gd3+ and Dy3+ with the Schiff base pyridine-2-carboxaldehyde-4-aminoantipyrine and different anions such as acetate, chloride, nitrate and thiocyanate. The analytical data include elemental analysis, molecular mass determination, conductivity, magnetic moment, spectral, thermal and antimicrobial studies. The composition of these complexes is found to be [Ln(P2CA4AAP)2(an)3], where Ln = La, Pr, Nd, Sm, Gd and Dy and an = acetate, chloride, nitrate and thiocyanate. In these complexes the primary ligand acts as a neutral tridentate ligand, the secondary ligands, viz., the monovalent acetate, chloride, nitrate and thiocyanate anions act as unidentate.